2017
DOI: 10.1007/jhep11(2017)101
|View full text |Cite
|
Sign up to set email alerts
|

Flavours and infra-red instability in holography

Abstract: With a simple gravitational model in five dimensions, defined by Einsteingravity with a negative cosmological constant, coupled to a Dirac-Born-Infeld and a ChernSimons term, we explore the fate of BF-bound violation for a probe scalar field and a fluctuation mode of the corresponding geometry. We assume this simple model to capture the dynamics of a strongly coupled SU(N c ) gauge theory with N f fundamental matter, which in the limit O (N c ) ∼ O (N f ) and with a non-vanishing matter density, is holographic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The pioneer work on this was done by [32] where D7 brans were embedded in the AdS geometry in the probe limit to ignore the back reaction on the target space. A variety of interesting issues has been looked upon with flavor branes using gauge/gravity duality in [33] [34] [35] [36].…”
Section: Resolved Conifold and D7 Brane Embeddingmentioning
confidence: 99%
“…The pioneer work on this was done by [32] where D7 brans were embedded in the AdS geometry in the probe limit to ignore the back reaction on the target space. A variety of interesting issues has been looked upon with flavor branes using gauge/gravity duality in [33] [34] [35] [36].…”
Section: Resolved Conifold and D7 Brane Embeddingmentioning
confidence: 99%
“…We intend to explore the solution space of the proposed action. The primary motivation for the inclusion of a Chern-Simons term can be drawn from the observation made in [10], in which it was demonstrated that, by tuning the parameter (N f /N c ), one may interpolate between a spatial modulation instability and a superconducting instability, similar to the physics of QCD at large N c and large N f [11]. Thus, we will treat the Newton's constant, the putative brane tension and the Chern-Simons coefficients which appear in defining the action of the theory to be free, and we will explore the nature of various exact analytical solutions, as one varies these parameters.…”
Section: Introduction and Conclusionmentioning
confidence: 99%